Gaps in DNA sequence libraries for Macaronesian marine macroinvertebrates imply decades till completion and robust monitoring. Issue 10 (18th June 2021) - Vieira, Pedro E.; Lavrador, Ana S.; Parente, Manuela I.; Parretti, Paola; Costa, Ana C.; Costa, Filipe O.; Duarte, Sofia
Abstract: Aim: DNA metabarcoding has great potential to improve biomonitoring in island's marine ecosystems, which are highly vulnerable to global change and non‐indigenous species (NIS) introductions. However, the depth and accuracy of the taxonomic identifications are mainly dependent on reference libraries containing representative and reliable sequences for the targeted species. In this study, we evaluated the gaps in the availability of DNA sequences and their accuracy for macroinvertebrates inhabiting Macaronesia's shallow marine habitats. Location: Macaronesia (Azores, Madeira, Selvagens, Canaries). Methods: Checklists of marine invertebrates occurring above 50 m depth were compiled using public databases and published checklists. The availability of cytochrome c oxidase subunit I (COI) and 18S rRNA (18S) gene sequences was verified in BOLD and GenBank. Finally, COI data were audited to check the congruence between morphospecies and Barcode Index Numbers (BINs). Results: The taxonomic coverage of different phyla was greater for COI but unbalanced and variable among archipelagos. NIS were better represented in genetic databases (up to 73% and 59%, for COI and 18S, respectively) than native species (up to 47% and 31%, for COI and 18S, respectively). NIS displayed a higher number of discordant records, and native species, a higher quantity of cases of multiple BINs. Notably, DNA sequences generated from specimens collected from Macaronesia were found in less than 10% of the species. Projection of the rates of accretion of DNA sequences suggests that decades will be needed to complete these reference libraries. Main conclusions: The level of completion of reference libraries for Macaronesia's marine macroinvertebrates is generally poor. Without a solid effort to speed up the production of sequence data (i.e. generate more DNA barcodes), the ability to employ DNA‐based biomonitoring of such vulnerable fauna is compromised. The high levels of suspected hidden diversity further deepen the expected gaps and reinforce the vulnerability of this endemism‐rich fauna.